Glycaemic control and antidiabetic therapy in patients with diabetes mellitus and chronic kidney disease: cross-sectional data from the German Chronic Kidney Disease (GCKD) cohort - Busch, Martin; Sommerer, Claudia (BMC nephrology, 2016)
Diabetes mellitus (DM) is the leading cause of end-stage renal disease. Little is known about practice patterns of anti-diabetic therapy in the presence of chronic kidney disease (CKD) and correlates with glycaemic control. We therefore aimed to analyze current antidiabetic treatment and correlates of metabolic control in a large contemporary prospective cohort of patients with diabetes and CKD.